The Impact of the Family Hope Program (PKH) on Household Financial Well-Being: The Moderating Role of Facilitators - Saputra, Edi; Goso, Goso; Duriani, Duriani (Universitas Muhammadiyah Pontianak, 2025)
This study examines the effect of the Family Hope Program (PKH) on the financial well-being of households in Luwu Utara Regency, with a focus on the role of facilitators as a moderating variable. Using a quantitative approach, data were collected through questionnaires distributed to 100 PKH beneficiaries and analyzed using moderation regression analysis. The findings show that PKH significantly enhances household financial well-being, although the facilitators' role tends to weaken this effect. The study contributes to understanding the financial impact of PKH and highlights the need for improved facilitation to optimize program outcomes.